PENGARUH KURS RUPIAH, TINGKAT SUKU BUNGA, DAN TINGKAT PENGANGGURAN TERHADAP HARGA SAHAM PADA PERUSAHAAN SUB SEKTOR PERTAMBANGAN MINYAK DAN GAS BUMI YANG TERCATAT DI BURSA EFEK INDONESIA PERIODE 2012-2017 - Atika Puspita Dewi; Salamatun Asakdiyah (Jurnal Fokus Manajemen Bisnis, 2018)
The monetary situation and the movement of macroeconomic variables are things  that  must be considered  an  investor  in  the  stock  trading activity in a country. The economic  situation  and  fluctuations  in  macro  variables  in  one country  can  affect  the  stock  price,  including  the  oil  and  gas  mining  sub-sector. This  study aimed to examine  the effect of  macroeconomic variables, namely exchange rate, interest rate, and unemployment rate to stock prices.  This study uses quantitative methods. The population in this study are all oil and gas mining sub-sector  companies  listed  in  Indonesia  Stock  Exchange  in  the  period  2012-2017. Sample selection technique is by using purposive sampling method. Based on  predetermined  criteria,  acquired 7 oil  and  gas  mining  sub-sector  companies sampled in this study. Data analysis techniques in this study using multiple linear regression analysis.  The results showed that the variables  simultaneously exchange  rate, interest rate, and  unemployment rate significant effect on stock price of oil and gas mining sub-sector  companies. Partially, variable Exchange Rate and Interest  Rate was  a  significant  influence  on stock price, while the variable Unemployment Rates no significant influence on stock price.